2006
DOI: 10.1177/105268460601600404
|View full text |Cite
|
Sign up to set email alerts
|

Licensed but Not Leading: Issues Influencing Individuals’ Pursuit of the Secondary Principalship

Abstract: In this study, we used survey research methods to examine (1) factors that motivated educators in the state of Iowa who held administrative licensure (125 females, 164 males) to actively pursue secondary principalship positions and (2) aspects that dissuaded them from applying. Respondents rated 10 factors that potentially motivated them to pursue administrative licensure, 36 factors related to perceived barriers to pursuing the principalship, and 5 questions related to perceived quality of leadership preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
1
8
2
Order By: Relevance
“…What are their motives for entering the principalship? It was hypothesized that, in line with previous research (Friesen et al, 1983;Morton, 2011;Schutte and Hackmann, 2006;Su et al, 2003), intrinsic reasons would be considered as the most important ones for becoming a principal.…”
Section: Objectives and Hypothesesmentioning
confidence: 73%
See 2 more Smart Citations
“…What are their motives for entering the principalship? It was hypothesized that, in line with previous research (Friesen et al, 1983;Morton, 2011;Schutte and Hackmann, 2006;Su et al, 2003), intrinsic reasons would be considered as the most important ones for becoming a principal.…”
Section: Objectives and Hypothesesmentioning
confidence: 73%
“…SDT distinguishes between amotivation -lack of motivation; intrinsic motivation -doing an activity for the sake of it, because of the inherent satisfaction it produces; and several forms of extrinsic motivation -doing an activity for instrumental reasons. Previous research indicated a more intrinsic than extrinsic motivation for principalship in American, Canadian, and Australian principals (Friesen et al, 1983;Morton, 2011;Schutte and Hackmann, 2006;Su et al, 2003). Su et al (2003), for example, asked a sample of Australian and American principals about their reasons for becoming principals, and found some commonalities: "to have a high paying job" and "to have job security and a steady income" were rated by both as not very important, and "to work with teachers in school improvement efforts" and "to have an impact in school restructuring" were rated by both as the more important reasons.…”
Section: Principals' Entry Motivationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Pounder and Merrill (2001) attempted to link desire for principalship with a number of job factors such as 'probability of being offered the job', 'desire to achieve', 'extra time demands of the job' and 'salary benefits', but these were more about possible benefits than role requirements. A more direct link between role and applicant expectations was reported by Schutte and Hackmann (2006). Their 290 respondents considered 'inadequate administrative skills', 'lack of personal experience', 'highly political position', and 'tremendous conflict associated with this position' as dampening their principalship desire.…”
Section: Related Literaturementioning
confidence: 87%
“…Today, the principal is viewed as a leader charged with the function of initiating change by raising the level of expectations for both teachers and students (Tschannen-Moran & Gareis, 2004); developing a caring community in the school (Sergiovanni, 1999); exercising effective instructional leadership (Gurr, Drysdale, & Mulford, 2006;Schutte & Hackmann, 2006), site baseddecision-making (Whitaker, 2003); and spending more time with parents and community (Kochan, Spencer, Matthews, 2000), among others. Today, the principal is viewed as a leader charged with the function of initiating change by raising the level of expectations for both teachers and students (Tschannen-Moran & Gareis, 2004); developing a caring community in the school (Sergiovanni, 1999); exercising effective instructional leadership (Gurr, Drysdale, & Mulford, 2006;Schutte & Hackmann, 2006), site baseddecision-making (Whitaker, 2003); and spending more time with parents and community (Kochan, Spencer, Matthews, 2000), among others.…”
mentioning
confidence: 99%